Test assessment of the development of kickboxers' coordination abilities at the stage of sportsmanship improvement - Grahov, I. A.; Zebzeev, V. V.; Zdanovich, O. S.; Chernova, G. M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a set of methods for assessing the development of kickboxers' coordination abilities at the stage of improving sportsmanship.